Therapeutic mammaplasty is a safe and effective alternative to mastectomy with or without immediate breast reconstruction. Issue 7 (19th February 2020) - Potter, S.; Trickey, A.; Rattay, T.; O'Connell, R. L.; Dave, R.; Baker, E.; Whisker, L.; Skillman, J.; Gardiner, M. D.; Macmillan, R. D.; Holcombe, C.; ,
Abstract : Background: Therapeutic mammaplasty (TM) may be an alternative to mastectomy, but few well designed studies have evaluated the success of this approach or compared the short‐term outcomes of TM with mastectomy with or without immediate breast reconstruction (IBR). Data from the national iBRA‐2 and TeaM studies were combined to compare the safety and short‐term outcomes of TM and mastectomy with or without IBR. Methods: The subgroup of patients in the TeaM study who underwent TM to avoid mastectomy were identified, and data on demographics, complications, oncology and adjuvant treatment were compared with those of patients undergoing mastectomy with or without IBR in the iBRA‐2 study. The primary outcome was the percentage of successful breast‐conserving procedures in the TM group. Secondary outcomes included postoperative complications and time to adjuvant therapy. Results: A total of 2916 patients (TM 376; mastectomy 1532; mastectomy and IBR 1008) were included in the analysis. Patients undergoing TM were more likely to be obese and to have undergone bilateral surgery than those having IBR. However, patients undergoing mastectomy with or without IBR were more likely to experience complications than the TM group (TM: 79, 21·0 per cent; mastectomy: 570, 37·2 per cent; mastectomy and IBR: 359, 35·6 per cent; P  < 0·001). Breast conservation was possible in 87·0 per cent of patients who had TM, and TM did not delay adjuvant treatment. Conclusion: TM may allow high‐risk patients who would not be candidates for IBR to avoid mastectomy safely. Further work is needed to explore the comparative patient‐reported and cosmetic outcomes of the different approaches, and to establish long‐term oncological safety. Abstract : Therapeutic mammaplasty (TM) may be an alternative to mastectomy, but few well designed studies have evaluated the success of this approach or compared the short‐term outcomes of TM with those of mastectomy with or without immediate breast reconstruction (IBR). In this pooled analysis of 2916 patients from the TeaM and iBRA‐2 studies, TM was associated with significantly fewer complications than mastectomy with or without IBR, and allowed almost 90 per cent of women to avoid mastectomy. TM may be a safe and effective alternative to mastectomy, especially in high‐risk women who may not be offered IBR, but further work including patient‐reported outcomes and cost‐effectiveness is required before definitive recommendations for best practice can be made. Increasing breast conservation Abstract : Antecedentes: La mamoplastia terapéutica ( therapeutic mammaplasty, TM) puede ser una alternativa a la mastectomía, pero hay pocos estudios bien diseñados que hayan evaluado el éxito de esta estrategia o hayan comparado los resultados a corto plazo de la TM con la mastectomía con o sin (+/‐) reconstrucción mamaria inmediata ( immediate breast reconstruction, IBR). Para comparar la seguridad y los resultados a corto plazo de la TM y la mastectomía +/‐ IBR se combinaron los datos de los estudios nacionales iBRA‐2 y TeaM. Métodos: En el estudio TeaM se identificó el subgrupo de pacientes al que se realizó una TM para evitar la mastectomía y se compararon los datos demográficos, las complicaciones, los resultados oncológicos y el tratamiento adyuvante con las pacientes sometidas a mastectomía +/‐ IBR del estudio iBRA‐2. La variable principal fue el porcentaje de éxito de la cirugía conservadora de mama en el grupo TM. Las variables secundarias fueron las complicaciones postoperatorias y el intervalo de tiempo hasta el inicio del tratamiento adyuvante. Resultados: Se incluyeron en el análisis 2.916 pacientes (TM n = 376; mastectomía n = 1.532; IBR n = 1.008). La TM era más frecuente en pacientes obesas o en las sometidas a cirugía bilateral en comparación con las pacientes con IBR. Sin embargo, las pacientes sometidas a una mastectomía +/‐ IBR tenían más probabilidades de desarrollar complicaciones que las del grupo TM (TM n = 79, 21, 0%; mastectomía n = 570, 37, 2%; mastectomía y IBR n = 359, 35, 6%; P < 0, 001). La conservación de la mama fue posible en el 87% de las pacientes con TM y el procedimiento no retrasó el inicio del tratamiento adyuvante. Conclusión: La TM puede permitir que pacientes de alto riesgo que no serían candidatas a IBR eviten la mastectomía de una forma segura. Se necesitan más trabajos para comparar los resultados percibidos por las pacientes y los estéticos de las diferentes estrategias terapéuticas y establecer la seguridad oncológica a largo plazo.